Strategi Pengembangan Pondok Pesantren Darul Ma’arif Nahdlatul Ulama Rejang Lebong Melalui Kaderisasi SDM - Fajariah Fajariah; Waskito Rahman; Tri Saputra; Irwan Fathurrochaman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to discover the strategy for developing the Darul Ma'arif Nahdlatul Ulama Islamic Boarding School in Rejang Lebong through HR cadre formation which is very necessary. The research method used is a qualitative descriptive approach. Data collection methods include observation, interviews, and documentation studies. In this research, the management of the Darul Ma'arif Nahlatul Ulama Islamic Boarding School acted as an informant. The results of implementing good strategic management starting from preparation, coaching, processing, and supervision have provided positive results in improving the quality of human resources and development of the Darul Ma'arif Nahdlatul Ulama Rejang Lebong Islamic Boarding School. These include: First, Optimizing Character, Second, Optimizing Caring, Third, Optimizing Collaboration, Fourth, Optimizing Critical Thinking. However, the implementation of this strategy still faces many obstacles, such as a lack of funds for cadre formation training, as well as inadequate time management. In conclusion, the Darul Maarif Nahdlatul Ulama Islamic Boarding School development strategy through HR cadre formation has implemented optimal strategic management, which is an important step in the process of maximizing an activity carried out, so that this step is expected to be able to realize the desired or desired benefits. Keywords: Development, Islamic Boarding School, Strategy, SDM,